Perbedaan Konsentrasi Bahan Herbal Terhadap Derajat Keasaman, Kadar Air dan Kadar Lemak Telur Asin Herbal - Ridwan Fauzi; Putri Dian Wulansari; Andri Kusmayadi (Bulletin of Applied Animal Research, 2022)
Eggs are one of the foodstuffs derived from poultry that have high nutritional content but are easily damaged due to the short durability of eggs. One solution that can be done is by salting the eggs into salted egg products. Salted eggs added with herbal ingredients to salting media are thought to prolong the durability of eggs and improve the quality of herbal salted eggs. This study aims to determine the effect of adding herbal ingredients with different concentrations on the quality of herbal salted eggs in terms of acidity (pH), water content and fat content. The study was conducted experimentally using a completely randomized design (CRD) with 5 treatments and each was replicated 6 times. The treatment of this study was the difference in concentration of 3 combinations of herbal ingredients used consisting of garlic, bay leaf, and sappan wood respectively by 0% (P0), 2.5% (P1), 5.0% (P2), 7 ,5% (P3), and 10% (P4). The results of this study showed that the use of herbal ingredients had a significant effect (P<0.05) on pH, while the parameters of water content and fat content had no significant effect (P>0.05). The P1 treatment (2.5% of herbal ingredients) produced the same pH value as the control treatment.